Effectiveness of Nano Spray From Extract of Kelubut Leaf (Passiflora foetida L.) as Antibiofilm on catheters of Patients with Urinary Tract Infection - Hasyrul Hamzah; Nur Atika Astriani; Norma Feti Farida; Lila Zulfa Kamilah; Aryantinur Azizah; Fathur Rahman (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Catheter-associated urinary tract infections (CAUTI) have increased significantly every year. Approximately 70-80% of these infections involve biofilms. This study aims to determine the effectiveness of nano spray formula of kelubut leaf extract in inhibiting and eradicating biofilm formation on catheters. Kelubut (Passiflora foetida L.) leaf extract was obtained through maceration process to obtain useful compounds. Antibiofilm activity was assessed using microbroth dilution, with scanning electron microscopy for visualization. The nano spray formulation activity of kelubut (Passiflora foetida L.) leaf extract was able to inhibit biofilm growth by (77.74% ± 0.01), while ciprofloxacin was slightly more effective with a value of (80.22% ± 0.01). SEM analysis confirmed the ability of the kelubut leaf extract nanospray formulation to inhibit and damage Escherichia coli biofilms. The nano spray formulation of kelubut leaf extract (Passiflora foetida L.) coded NS1 is able to inhibit biofilm formation activity on catheters and has the potential to be developed as an antibiofilm candidate against bacteria that cause urinary tract infections.